Impact of an educational programme in Portuguese people with diabetes. Issue 2 (June 2019) - Sousa, Maria Rui; Pereira, Filipe; Martins, Teresa; Rua, Isabel; Ribeiro, Ilda; Cerdeira, Catarina; Lopes, Laurinda; Sèvegrand, Clara; Santos, Carla
This study, conducted in the north of Portugal, is the result of a group of nurses' intent to develop a closer and meaningful person-centered care for patients with diabetes, empowering them with skills to better manage their therapeutic regimen. Through a participatory action research process, the group of nurses involved in this study, reflected on the current healthcare enabling them an in-depth analysis of the best scientific evidence, aiming to design context tailored solutions, which would contribute to patients' empowerment. Through a longitudinal study developed over several stages, the nurses outlined the educational programme Living in harmony with diabetes, which was applied to 85 patients with diabetes mellitus type 2. The programme had a positive impact on the psychosocial variables, in self-care behaviour and in the metabolic control, helping patients to better cope with their disease and have greater control over their health condition. Throughout the process of participatory action research, the nurses were able to increase their self-efficacy and empowerment on person-centered care implementation.